Meningkatkan Martabat Guru: Strategi Pengakuan dan Penghargaan Profesi Kependidikan di Era Digital - Islawati, Islawati; Samsuddin, Yati Bt (Lembaga Intelektual Muda (LIM) Maluku, 2025)
The digital era presents significant opportunities and challenges for the teaching profession, particularly in terms of recognition and appreciation for their contributions. Teachers are expected to adapt to technology to improve the quality of learning but often face obstacles such as lack of training, limited infrastructure, and non-inclusive reward systems. This article aims to explore the challenges faced by teachers in the digital era and propose strategies to enhance the dignity of the profession. The study was conducted through a literature review collected from academic databases such as Sinta and Google Scholar, covering the period 2018-2024, with a focus on sustainable technology training, holistic contribution-based reward systems, and cross-sector collaboration. Thematic analysis techniques were used to identify key themes such as the challenges of technology adaptation, unequal reward systems, and the humanistic roles of teachers. The results indicate that recognizing the humanistic roles of teachers, along with technological support and equitable rewards, is crucial for maintaining their dignity. This research provides concrete recommendations to support teacher professionalism in the digital era